Combined Therapy With Adipose-Derived Mesenchymal Stem Cells and Ciprofloxacin Against Acute Urogenital Organ Damage in Rat Sepsis Syndrome Induced by Intrapelvic Injection of Cecal Bacteria. (13th April 2016) - Sung, Pei-Hsun; Chiang, Hsin-Ju; Chen, Chih-Hung; Chen, Yi-Ling; Huang, Tien-Hung; Zhen, Yen-Yi; Chang, Meng-Wei; Liu, Chu-Feng; Chung, Sheng-Ying; Chen, Yung-Lung; Chai, Han-Tan; Sun, Cheuk-Kwan; et al.
Abstract : Combined therapy with autologous adipose-derived mesenchymal stem cells and ciprofloxacin was found to be superior to either therapy alone in improving the outcome in a rodent sepsis model. Abstract: : We hypothesized that combined treatment with autologous adipose-derived mesenchymal stem cell (ADMSC) and ciprofloxacin is superior to ciprofloxacin only in reducing sepsis-induced urogenital organ damage and mortality in rat sepsis syndrome (SS) caused by intrapelvic injection of cecal bacteria (1.0 × 10 4 cells per milliliter; total, 5.0 ml). Male Sprague-Dawley rats ( n = 60) equally divided into group 1 (sham-control), group 2 (SS), group 3 (SS-ADMSC [5.0 × 10 5 intravenously at 0.5, 6, and 18 hours after sepsis induction]), group 4 (SS-ciprofloxacin [3.0 mg/kg, b.i.d.] for 5 days), and group 5 (SS-ADMSC-ciprofloxacin) were sacrificed by day 5. Mortality rate and creatinine level were highest in group 2 and lowest in group 1 and significantly higher in groups 3 and 4 than those in group 5, but there was no difference between groups 3 and 4 (all p < .005). The kidney injury score, inflammatory biomarker expressions at protein (tumor necrosis factor-1α, nuclear factor-κB, matrix metallopeptidase-9, regulated on activation, normal T-cell expressed and secreted, interleukin-1β) and cellular (CD14+, migratory inhibitor factor positive, CD68+) levels in kidneys and urinary bladder were lowest in group 1 and highest in group 2, higher in group 4 than in groups 3 and 5, and higher in group 3 than in group 5 (all p < .001). Protein expressions of apoptosis (Bax, cleaved caspase 3 and poly[ADP-ribose] polymerase 1, p21 protein [Cdc42/Rac]-activated kinase 2) and oxidative stress (oxidized protein, NADPH oxidase (NOX)-1, NOX-2) in these organs showed an identical pattern compared with that of inflammation in all groups (all p < .001). In conclusion, ADMSC-assisted ciprofloxacin therapy offered an additional benefit by reducing acute urogenital organ damage in rat. Significance: Autologous adipose-derived mesenchymal stem cell-assisted ciprofloxacin therapy offered an additional benefit by reducing acute urogenital organ damage in rats.